The Role of Environmental Governance, Public Policy Innovation, and Green Investment on the Performance of Industrial Estate Development in Indonesia - Halomoan Hutajulu (Westscience Press, 2026)
The development of industrial estates plays a strategic role in supporting economic growth and industrial competitiveness in emerging economies, including Indonesia. However, increasing environmental pressures and sustainability demands require industrial estate development to be supported by effective governance, innovative public policies, and environmentally oriented investment. This study aims to examine the effect of environmental governance, public policy innovation, and green investment on the performance of industrial estate development in Indonesia. A quantitative research approach was employed using primary data collected from 85 respondents involved in industrial estate management, regulation, and development. Data were gathered through a structured questionnaire measured on a Likert scale and analyzed using multiple linear regression with SPSS version 25. The results indicate that environmental governance has a positive and significant effect on industrial estate development performance, followed by public policy innovation and green investment. The regression model explains 54.9% of the variance in development performance, indicating a substantial explanatory power. These findings demonstrate that strong environmental governance, adaptive policy frameworks, and strategic green investment are critical drivers of sustainable and high-performing industrial estate development. This study provides empirical evidence to support sustainability-oriented industrial policies and offers practical implications for policymakers, industrial estate developers, and investors in promoting green and competitive industrial growth in Indonesia.